Prevalence of viral respiratory tract infections in children with asthma - Khetsuriani, Nino (J Allergy Clin Immunol, 2007)
BACKGROUND: Previous studies support a strong association between viral respiratory tract infections and asthma exacerbations. The effect of newly discovered viruses on asthma control is less well defined. OBJECTIVE: We sought to determine the contribution of respiratory viruses to asthma exacerbations in children with a panel of PCR assays for common and newly discovered respiratory viruses. METHODS: Respiratory specimens from children aged 2 to 17 years with asthma exacerbations (case patients, n = 65) and with well-controlled asthma (control subjects, n = 77), frequency matched by age and season of enrollment, were tested for rhinoviruses, enteroviruses, respiratory syncytial virus, human metapneumovirus, coronaviruses 229E and OC43, parainfluenza viruses 1 to 3, influenza viruses, adenoviruses, and human bocavirus. RESULTS: Infection with respiratory viruses was associated with asthma exacerbations (63.1% in case patients vs 23.4% in control subjects; odds ratio, 5.6; 95% CI, 2.7- 11.6). Rhinovirus was by far the most prevalent virus (60% among case patients vs 18.2% among control subjects) and the only virus significantly associated with exacerbations (odds ratio, 6.8; 95% CI, 3.2-14.5). However, in children without clinically manifested viral respiratory tract illness, the prevalence of rhinovirus infection was similar in case patients (29.2%) versus control subjects (23.4%, P > .05). Other viruses detected included human metapneumovirus (4.6% in patients with acute asthma vs 2.6% in control subjects), enteroviruses (4.6% vs 0%), coronavirus 229E (0% vs 1.3%), and respiratory syncytial virus (1.5% vs 0%). CONCLUSION: Symptomatic rhinovirus infections are an important contributor to asthma exacerbations in children. CLINICAL IMPLICATIONS: These results support the need for therapies effective against rhinovirus as a means to decrease asthma exacerbations.